2013
DOI: 10.1016/j.jagp.2013.01.015
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and Comorbid Symptoms of Older Adults Reporting Death Ideation

Abstract: Objective To determine whether death ideation in late life is associated with markers of elevated risk for suicide, or reflects normal psychological processes in later life. Design/Setting Population based cross sectional study in Gothenburg, Sweden. Participants The sample consists of 345 men and women aged 85 (born 1901-02) and living in Gothenburg, Sweden. Main Outcome Measures The Paykel Scale measured the most severe level of suicidality over an individual’s lifetime. Other key measures were severit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(25 citation statements)
references
References 32 publications
0
25
0
Order By: Relevance
“…Rather, we suggest that more research is needed that examines the effectiveness of selective interventions that target groups at risk but well before the development of the acutely suicidal state, as intervening at this point in the trajectory toward suicide may be “too late” for some older adults. Some studies exist, including the Tele Help—Tele Check study described above, as well as a study we are conducting with our colleagues of the effectiveness of peer companionship for socially disconnected older adults (Van Orden et al, 2013), but more work is needed. Finally, all forms of intervention—universal, selective, and indicated—play an important role in suicide prevention in later life.…”
Section: Lethality Of Late-life Suicidal Behaviormentioning
confidence: 99%
See 1 more Smart Citation
“…Rather, we suggest that more research is needed that examines the effectiveness of selective interventions that target groups at risk but well before the development of the acutely suicidal state, as intervening at this point in the trajectory toward suicide may be “too late” for some older adults. Some studies exist, including the Tele Help—Tele Check study described above, as well as a study we are conducting with our colleagues of the effectiveness of peer companionship for socially disconnected older adults (Van Orden et al, 2013), but more work is needed. Finally, all forms of intervention—universal, selective, and indicated—play an important role in suicide prevention in later life.…”
Section: Lethality Of Late-life Suicidal Behaviormentioning
confidence: 99%
“…In one paper, we examined this question in a sample of 85 year olds from Sweden (Van Orden, Simning, Conwell, Skoog, & Waern, 2013). We found that the majority of older adults who endorsed passive suicide ideation within the last month also endorsed either active thoughts of killing themselves in their lifetimes or significant depressive or anxious symptomatology in the past month, indicating that passive suicide ideation was closely linked with indicators of suicide risk.…”
Section: Thoughts Of Death In Later Lifementioning
confidence: 99%
“…The trends for death by suicide in older populations have not diminished over three decades [2], despite several years of research to better understand the predictors and precursors of late life suicide, as well as intervention research demonstrating the positive effects of depression intervention on reductions in suicidal ideation[3-5] . It is well known that 90% of older people who take their lives suffered from a psychiatric disorder[6] with depressive disorders being the most common psychiatric diagnoses of elderly suicide victims[7]. Furthermore, late life suicidal ideation is a risk factor for suicide [4, 8, 9], and executive dysfunction[10, 11], in particular impulsivity [12-14], and impairments in risk-sensitive decision making[14, 15] are associated with greater suicidal ideation in older adults.…”
Section: Introductionmentioning
confidence: 99%
“…Late-life anxiety symptoms have been linked with many adverse outcomes such as death ideation (Van Orden et al 2013), nursing home placement (Gibbons et al 2002), poor cognitive performance (Beaudreau et al 2013), functional impairment (Brenes et al 2008; Porensky et al 2009), and poor general health (Losada et al 2014). …”
mentioning
confidence: 99%